Quest Technology as a Means of Forming the Life Successfulness of Senior School Pupils - Necherda, Valeriia (Theoretical and Methodical Problems of Children and Youth Education, 2025)
The purpose of the research is to substantiate the potential of quest technology as a means of forming the life successfulness of pupils and to present the successful experience of using the quest in the educational process of experimental secondary education institutions. The objectives of the mentioned research are to generalize data concerning the quest in educational science and practice, in particular, in the formation of the life successfulness of pupils and to highlight the features of the implementation of the quest in the practice of forming the life successfulness of senior school pupils of experimental secondary education institutions of the Division of Educational Projecting of the Institute of Problems on Education of the National Academy of Educationаl Sciences of Ukraine. As theoretical methods, a systemic and structural analysis of domestic and foreign psychological and pedagogical sources on the problem of introducing quest technology into the educational process of secondary education institutions was selected, as well as theoretical generalization, comparison, and reinterpretation of the obtained data to formulate the research conclusions. The empirical methods were the “peer-to-peer” method, “brainstorming”, discussion, conversation, mini-lecture, scribing method and infographic method, with their assistance the quest technology was introduced into the practice of forming the life successfulness of senior school pupils. The theoretical and methodological basis of the research was the acmeological, axiological, competency-based, and project-technological approaches, which logically complemented each other. The author outlined the main features of the quest as an innovative pedagogical technology and noted its compliance with the needs of a modern senior school pupil. The article examines the theoretical and practical blocks of the quest “Stress resistance is the key to life success”, it is noted that the practical block of the quest contributed to improving the skills of awareness and management of emotions, increasing self-esteem and developing creativity of pupils, reducing the level of anxiety of pupils; the researcher also focused on the destructive impact of stress and identified the simplest ways to counteract stress and find resource states. The proposed research identifies factors that provoke stress among pupils, notes the advantages of the Success Diary, and indicates the need to develop stress resistance as an essential skill for a successful senior school pupil in the conditions of military rule and post-war reality. Based on the obtained results, it was noted that the introduction of quest technology into the practice of forming life successfulness, stress resistance, in particular, of senior school pupils of experimental secondary education institutions contributed to the creation of conditions for pupils to demonstrate activity, imagination and creative initiative, experience positive emotions, gain experience in constructive dialogue with peers and team work, comprehend socially significant values, and effectively adapt to the educational environment.